Concurrent validity of lower limb kinematics between markerless and marker-based motion capture systems in gait and running - Molina-Molina, A.; Mercado-Palomino, E.; Delgado-García, G.; Millán-Sánchez, A.; Ureña Espa, A.; Soto-Hermoso, V. M. (ISBS Proceedings Archive (Michigan), 2017)
The goal of this study was to evaluate the accuracy of a markerless silhouette-based tracking and hybrid tracking against traditional marker tracking. Different speeds in gait and running conditions were analysed. In the literature, studies most often make use of low cost rather than high performance systems. Markerless systems allow us to evaluate in the most natural conditions. Very high correlations were obtained depending on the joint. The use of markerless tracking is still new regarding motion analysis in sports or for clinical purposes. This technology could be a very good solution for clinical rehabilitation and real sports situations.